Assessment of prophylactic heparin infusion as a safe preventative measure for thrombotic complications in pediatric kidney transplant recipients weighing <20 kg. (6th June 2019) - Kim, Jin K.; Chua, Michael E.; Teoh, Chia Wei; Lee, Min Joon; Kesavan, Amre; Hebert, Diane; Lorenzo, Armando J.; Farhat, Walid A.; Koyle, Martin A.
Abstract: Small‐sized kidney recipients (<20 kg) are at high risk of allograft vessel thrombosis. HP has been used to mitigate this risk but may infer an increase in bleeding risks. Therefore, we aim to determine whether HP is a safe means to prevent thrombosis in small kidney transplant patients by comparing those who have received HP and those who have NHP. A retrospective review of patients < 20 kg who underwent kidney transplant in our institution from 2000 to 2015 was performed. At our institution, unfractionated heparin 10 units/kg/hour is used as HP since 2009. Patients at increased risk of thrombosis (previous thrombosis, thrombophilia, nephrotic syndrome) and bleeding (therapeutic doses of heparin, diagnosis of coagulopathy) were excluded. Fifty‐six patients were identified (HP n = 46; NHP n = 10). Baseline demographics were similar between HP and NHP. There was no statistical difference in frequency of transfusions, surgical re‐exploration, or thrombotic events between HP and NHP. The HP group was more likely to have drop in Hb > 20 g/L (67.4% vs 30.0%, P = 0.038), and those who had drop in Hb > 20 g/L were more likely to also require pRBC transfusions (63.0% vs 20.0%, P = 0.017). Within the HP group, those who had bleeding complications had similar Hb levels as those who did not at baseline and post‐transplant. Outcomes in the HP and NHP groups were no different with respect to thrombosis or significant bleeding complications requiring pRBC transfusions or surgical intervention. Future prospective studies are required to investigate the balance of preventing thrombosis and risks of pRBC transfusions for small‐sized kidney recipients.